Organ preservation in rectal cancer: current status and future perspectives. (August 2015) - Putte, Dirk Vande; Nieuwenhove, Yves Van; Willaert, Wouter; Pattyn, Piet; Ceelen, Wim
With the introduction of population screening initiatives, more patients may be amenable to local, transanal excision (LE) of early-stage rectal cancer. The most important drawback of LE is the risk of understaging node-positive disease. The most powerful predictors of node-positive disease are lymphatic invasion, submucosal invasion depth and width, tumor budding and poor differentiation. Therefore, LE should be reserved for low-risk T1 tumors in those reluctant or unable to undergo major surgery. Neoadjuvant chemoradiation followed by LE for T2 tumors allows adequate local control, and is currently being compared with anterior resection alone in randomized trials. A mere watchful waiting approach has been proposed in clinical complete responders to chemoradiation. However, given the very poor accuracy of current imaging modalities to predict a true pathological complete response, this strategy should not be offered outside of well-controlled trials.